Umbilical cord drainage versus intraumbilical cord oxytocin injection in management of third stage of labour - Miran, Najmah M.; Dawood, Farah S. (Journal of the Faculty of Medicine Baghdad, 2017)
Background: Postpartum hemorrhage is an important cause of maternal morbidity and mortality. Considerable difference of opinion exist regarding the optimal approach to the management of the 3rd stage of labour, practice varies between countries &between units. Objectives: To evaluate the effectiveness of intra umbilical vein injection of oxytocin and umbilical cord driange in shortening the duration of third stage of labour. Patient and Methods: In this randomized controlled study, 100 women were enrolled in this study they divided into three groups. (Group 1 ,N =30 )received 20 units of oxytocin diluted in 20 ml 0.9% saline solution injected in the umbilical vein after clamping.(Group 2, N = 34) placental cord drainage.(Group 3, N= 36) with no intervention. The primary outcome was mean duration of third stage of labor. Results: The third stage of labor was significantly shorter in group 1 and 2 as compared to group 3. Groups 1 shorten the duration of third stage of labor by 3 min. and group 2 shorten the duration of third stage of labor by 4.27 min.There were no reports of need for manual removal of placenta or retained placenta. Conclusion: The use of intraumbilical injection of oxytocin and placental cord drainage in the third stage of labor significantly reduced the duration of the third stage.